Comparisons between Islamic banking products and conventional banking products: a study on personal loan Bank Rakyat and Maybank / Nur Hidayat Abdul Ghani - Abdul Ghani, Nur Hidayat (Faculty of Business and Management, 2011)
This study is about comparisons between Islamic Banking Products and Conventional Banking Products. A study on personal loan Bank Rakyat and Maybank. The problem statement is that Malaysia has through a rapid growth of Islamic Bank development, a conventional bank ought to rival with Islamic Bank to give a better offer’s to customer. The purpose of this study is to identify the comparisons between Islamic banking products and Conventional banking products of personal loan Bank Rakyat and Maybank. These comparisons will be based on interest rate, concept and handling fee and charge of personal loan. In this study there have three research objectives which is to identify the interest rate offer by Bank Rakyat and Maybank, to find out concept of personal loan used by Bank Rakyat and Maybank and to determine the handling fee or charges for personal loan process by Bank Rakyat and Maybank. This study is a case study. The research method that be used by this study is primary and secondary method. Sources of primary data will gain for interview session while for secondary data gain from bank website, journals, annual report and pamphlets. The findings will focus on different of interest rate, concept and handling fee and charges. There is a different between Islamic Bank and Conventional Bank on personal loan products.